2001
DOI: 10.1093/carcin/22.11.1757
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination in extrachromosomal plasmid substrates is not suppressed by p53

Abstract: We and others reported previously that the tumor suppressor p53 down-regulates spontaneous homologous recombination in chromosomally integrating plasmid substrates, but how p53 affects homology-dependent repair of DNA double-strand breaks has not been established. Furthermore, it has been hypothesized that p53 may suppress homologous recombination by direct interaction with recombination intermediates, but it is not known whether p53 directly acts on extrachromosomal plasmid substrates. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Here, we found that p53À/À MEFs have more cells with RAD51 foci (Figure 2a), in agreement with a general increase in HR previously reported in p53 mutated cells (Bertrand et al, 1997;Mekeel et al, 1997;Xia et al, 1997;Saintigny et al, 1999;Willers et al, 2000;Saintigny and Lopez, 2002). However, we found that the numbers of HU-induced RAD51 foci were similar in p53 þ / þ and p53À/À MEFs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we found that p53À/À MEFs have more cells with RAD51 foci (Figure 2a), in agreement with a general increase in HR previously reported in p53 mutated cells (Bertrand et al, 1997;Mekeel et al, 1997;Xia et al, 1997;Saintigny et al, 1999;Willers et al, 2000;Saintigny and Lopez, 2002). However, we found that the numbers of HU-induced RAD51 foci were similar in p53 þ / þ and p53À/À MEFs.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is possible that p53 maintains stability of the genome through its interaction with RAD51. Support for this notion also comes from the observation that p53-deficient cells exhibit increased levels of HR and elevated levels of the RAD51 protein (Bertrand et al, 1997;Mekeel et al, 1997;Xia et al, 1997;Saintigny et al, 1999;Willers et al, 2000;Saintigny and Lopez, 2002). In addition, the lethality of RAD51 and RAD51L1 knockout mice can be suppressed by additional knockout of p53 (Lim and Hasty, 1996;Shu et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar results were obtained with extra-chromosomal assays. 32 Genetic disruption of p53 also did not lead to an increased rate of SCE in HCT-116 cells or in other human cell lines, 24,25 nor did it affect the frequency of meiotic crossover events in mice. 23 Together, these findings indicate that p53 has no direct role in suppressing HR mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…2,[27][28][29] The exact mechanism by which p53 discriminates between ectopic HR and allelic HR or SCE is unclear. However, the lack of p53's effect on allelic HR or SCE together with the demonstration that neither RAD51-dependent nor RAD51-independent HR involving extra-chromosomal DNA was affected by the p53 status of the cell 24,[30][31][32] indicate that p53 does not block DNA strand exchange reactions in cells, and that regulation of ectopic HR by p53 may be restricted to the highly-ordered chromatin structure. 32 The ability of p53 to alter chromatin structure and repress transcription, 33 together with the well established link between transcription repression and decreased efficiency of intra-chromosomal HR (reviewed in ref.…”
Section: Introductionmentioning
confidence: 98%